(untitled) (Fiep Bulletin - online, 2011)
Traumatic brain injury (TBI) is the leading cause of death and disability in industrialized countries. Among the major reasons we can mention car accidents, pedestrian accidents, motorcycle accidents, assaults, falls and injuries by level of firearm. TBI is classified as level of consciousness, determined by the Glasgow Coma Scale (GCS) as mild, moderate and severe, according to motor responses, verbal and eye opening. Objective: To describe the rate of elderly patients (over 60 years) traumatic brain injury admitted to the University Hospital of Paraná in 2009. Methods: This study was conducted to review analysis of 265 medical records of patients diagnosed with TBI admitted to the University Hospital of Western Paraná (HUOP) between January and December 2009, where data were collected as the leading causes of TBI, severity according to Glasgow Coma Scale, age, gender, duration of hospital stay, and also mortality. Results: We found that victims of TBI, predominantly males, 74.34% and the main age group affected were young adults (16-30 years) with 28.03%, and elderly patients over 60 years, had the lowest rate of 7.95% involvement. Automobile accidents were considered the leading cause of TBI totaling 47.18%, followed by falls (31.70%) and aggression (9.06%), and the elderly, the main cause of the falls were very level. Depending on the severity, 58.11% of the victims had mild head injuries, 29.43% and 8.31% moderately severe. Conclusion: Among patients hospitalized in 2009, TBI, 7.95% were elderly, thus representing the lowest incidence. Since we have not cause any comfort, but highlights the need for strengthening of preventive programs aimed at the elderly population, seeking more and more, reducing the percentage shown in this study.